Peran Kantin Kejujuran Untuk Menanamkan Pendidikan Anti Korupsi Pada Siswa : Studi Literature Review - Azizah Cahya Fajrin; Lely Ika Mariyati (Jurnal Adijaya Multidisplin, 2023)
In instilling character education from an early age, appropriate facilities and media are needed in realizing the creation of this education for students. Honesty is one of the character education that needs to be taught and instilled in every student. Honest attitude is part of the anti-corruption education that has been launched by the government. One of the media that can be used in teaching and familiarizing students with honesty is through the application of an honesty canteen. The honesty canteen was proclaimed by the KPK Institute as a learning medium to shape anti-corruption character in students. This study aims to determine the planting of anti-corruption education through the media of honesty canteens for students. This research was conducted in a descriptive qualitative manner. The type of research used in this study is a literatur review with a traditional type of review. The results of the analysis show that the honesty canteen as a medium for instilling anti-corruption education can be applied at all levels of education, from the elementary school level to the upper secondary level. In conclusion, anti-corruption education in schools needs to be carried out in an integrated manner with various themes of learning in the classroom and practical life in schools so that anti-corruption education can be well instilled in each student.